Novel, benign, solid catalysts for the oxidation of hydrocarbons - Ratnasamy, P; Raja, R; Srinivasi, D (Philosophical Transactions of the Royal Society A - Mathematical, Physical and Engineering Sciences, 2005)
The catalytic properties of two classes of solid catalysts for the oxidation of hydrocarbons in the liquid phase are discussed: (i) microporous solids, encapsulating transition metal complexes in their cavities and (ii) titanosilicate molecular sieves. Copper acetate dimers encapsulated in molecular sieves Y, AICM-22 and VPI-5 use dioxygen to regioselectively ortho-hydroxylate L-tyrosine to L-dopa, phenol to catechol and cresols to the corresponding o-dihydroxy and o-quinone compounds. Monomeric copper phthalocyanine and salen complexes entrapped in zeolite-Y oxidize methane to methanol, toluene to cresols, naphthalene to naphthols, xylene to xylenols and phenol to diphenols. Trimeric mu(3)-oxo-bridged Co/Mn cluster complexes, encapsulated inside Y-zeolite, oxidize para-xylene, almost quantitatively, to terephthalic acid. In almost all cases, the intrinsic catalytic activity (turnover frequency) of the metal complex is enhanced very significantly, upon encapsulation in the porous solids. Spectroscopic and electrochemical studies suggest that the geometric distortions of the complex on encapsulation change the electron density at the metal ion site and its redox behaviour, thereby influencing its catalytic activity and selectivity in oxidation reactions. Titanosilieate molecular sieves can oxidize hydrocarbons using dioxygen when loaded with transition metals like Pd, An or Ag. The structure of surface Ti ions and the type of oxo-Ti species generated on contact with oxidants depend on several factors including the method of zeolite synthesis, zeolite structure, solvent, temperature and oxidant. Although, similar oxo-Ti species are present on all the titanosilicates, their relative concentrations vary among different structures and determine the product selectivity.
Keywords: benign catalytic oxidations; encapsulated metal complexes; Solid catalysts; titanosilicate molecular sieves

Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves